2022
DOI: 10.1093/ibd/izac061
|View full text |Cite
|
Sign up to set email alerts
|

Association of C-reactive Protein and Partial Mayo Score With Response to Tofacitinib Induction Therapy: Results From the Ulcerative Colitis Clinical Program

Abstract: Background Tofacitinib is an oral, small molecule JAK inhibitor for the treatment of ulcerative colitis (UC). These post hoc analyses assessed associations between C-reactive protein (CRP), partial Mayo score (PMS), and efficacy outcomes during tofacitinib induction in UC. Methods Patients received tofacitinib 10 mg twice daily (BID) in an 8-week, phase 2 induction study and 2 identical, 8-week, phase 3 induction studies (OCT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
2
3
0
Order By: Relevance
“…17 Although literature suggests that CRP may not be sensitive enough to detect endoscopic activity in the quiescent disease, it was accurate in detecting response to therapy at week 1 in our study enrolling the moderately to severely active UC. Consistent with our results, it has been reported that CRP at weeks 2-4 predicted induction outcomes by IFX 7 or tofacitinib, 29 and CRP at day 3 was a predictor of colectomy in 30 days in acute severe UC treated with steroids. 30 Surgery or switching to other drugs is recommended if there is no improvement in 1 week in acute severe UC, 31 although such a decision making can be challenging especially when patients show marginal change.…”
Section: Discussionsupporting
confidence: 92%
“…17 Although literature suggests that CRP may not be sensitive enough to detect endoscopic activity in the quiescent disease, it was accurate in detecting response to therapy at week 1 in our study enrolling the moderately to severely active UC. Consistent with our results, it has been reported that CRP at weeks 2-4 predicted induction outcomes by IFX 7 or tofacitinib, 29 and CRP at day 3 was a predictor of colectomy in 30 days in acute severe UC treated with steroids. 30 Surgery or switching to other drugs is recommended if there is no improvement in 1 week in acute severe UC, 31 although such a decision making can be challenging especially when patients show marginal change.…”
Section: Discussionsupporting
confidence: 92%
“…These findings agreed with those described by Honap et al (21) who observed that younger age at treatment initiation and elevated CRP at baseline were independently associated with primary nonresponse. These findings are in line with those previously described in clinical trials, where both CRP and PMS at baseline were associated with short-term response, confirming that patients with higher inflammatory burden are at a higher risk of treatment failure (27). On the contrary, in OCTAVE 1 and 2 trials, the treatment effect was similar between those who had received previous treatment with an anti-TNF agent and those who had not (12).…”
Section: Discussionsupporting
confidence: 91%
“…Post hoc analyses of the OCTAVE trials [30] have identified potential predictors of response to tofacitinib [51][52][53][54].…”
Section: Predictions Based On Baseline Characteristicsmentioning
confidence: 99%
“…A more recent post hoc analysis of the OCTAVE induction studies [52] showed that CRP drop and PMS reduction at week 4 were associated with better outcomes in terms of clinical response (per unit odds ratio (OR) 0.86, 95% CI, 0.77-0.97, p = 0.0147, and OR 0.51, 95% CI 0.46-0.57, p < 0.0001, respectively), clinical remission (per unit OR 0.78, 95% CI, 0.67-0.91, p = 0.0020, and OR 0.46, 95% CI 0.40-0.54, p < 0.0001, respectively) and endoscopic improvement (per unit OR 0.66, 95% CI, 0.58-0.75, p < 0.0001, and OR 0.66, 95% CI 0.60-0.73, p < 0.0001, respectively) at week 8. CRP but not PMS was also associated with week-8 endoscopic remission (OR 0.62, 95% CI 0.53-0.73, p < 0.0001).…”
Section: Predictions Based On Baseline Characteristicsmentioning
confidence: 99%